2010
DOI: 10.1080/10916460802706463
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Archie's Parameters Determination Techniques

Abstract: An accurate determination of oil reserve in either undeveloped or in developed reservoirs represents the main task of petrophysicist and reservoir engineer. Input parameters of Archie's water saturation model in clean formation or suitable shaly water saturation model must be determined as accurately as possible. Archie's parameters a, m, and n are the most important parameters to be estimated affecting determination of water saturation, in addition to the empirical constants required for selected empirical sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
(8 reference statements)
0
7
0
1
Order By: Relevance
“…The reference parameter fields for the Archie's parameters m and n were generated using unconditional simulation based again on an exponential variogram model with anisotropy axis of 6,500 ft in the xdirection, and 6,200 ft in the y-direction, and are shown in Figure 5 [34]. The parameter values range between 1.6 and 2.4, ranges that are typically encountered for carbonate reservoirs [27], [34], [36].…”
Section: Iii1 Experimental Setupmentioning
confidence: 99%
See 3 more Smart Citations
“…The reference parameter fields for the Archie's parameters m and n were generated using unconditional simulation based again on an exponential variogram model with anisotropy axis of 6,500 ft in the xdirection, and 6,200 ft in the y-direction, and are shown in Figure 5 [34]. The parameter values range between 1.6 and 2.4, ranges that are typically encountered for carbonate reservoirs [27], [34], [36].…”
Section: Iii1 Experimental Setupmentioning
confidence: 99%
“…Relating electrical conductivity changes to the dynamics in the reservoir has proven to be significantly challenge in particular for carbonate reservoir formations [25]- [27]. While Archie's Law has been the standard relationship in the industry for decades, research [28]- [33] has shown that its parameters may significantly vary for different formations and rock types and hence need to be calibrated or estimated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, n is the saturation exponent and has the common value of 2 in strongly water-wet reservoir rocks. An exact computation of water saturation using modified Archie's law, Equation (2.10) is based on an accurate values of Archie's parameters a, m, and n. Hamada [55] presented three techniques to determine Archie's parameters. Other modifications of Archie's law can be found, e.g.…”
Section: Relationship Between Resistivity and Saturationmentioning
confidence: 99%